2011
DOI: 10.5424/fs/2011201-8924
|View full text |Cite
|
Sign up to set email alerts
|

Insect biodiversity reduction of pinewoods in southern Greece caused by the pine scale (Marchalina hellenica)

Abstract: This paper deals with the impact of the pine scale (Marchalina hellenica Gennadius, Hemiptera, Sternorrhyncha, Margarodidae) on the insect biodiversity of pinewoods in Attica, Greece. The comparison of biodiversities was done by estimating the biodiversity by the Ewens-Caswell V statistic in a set of nine sites each containing two linetransects. Transects pairs went through free and infested pinewoods from the pine scale and each one had several tenth hectare plots on both sides. The ecosystem temperature (= d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 2 publications
0
11
0
1
Order By: Relevance
“…Losses will be inevitably occurring during the time but it is important and profitable to maintain high effective population numbers for the keystone species (e.g. beech, fir, oak, pine) in order to conserve a rich biodiversity and high biodiversity quality In addition to the measures above, actions have been taken in order to increase and restore forest areas [18] [19] [52]: 1) reforestation plans (using native species and local provenances) for the restoration of fire destroyed forest areas;…”
Section: Adaptive Forest Management and Silviculture-conservation Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Losses will be inevitably occurring during the time but it is important and profitable to maintain high effective population numbers for the keystone species (e.g. beech, fir, oak, pine) in order to conserve a rich biodiversity and high biodiversity quality In addition to the measures above, actions have been taken in order to increase and restore forest areas [18] [19] [52]: 1) reforestation plans (using native species and local provenances) for the restoration of fire destroyed forest areas;…”
Section: Adaptive Forest Management and Silviculture-conservation Measuresmentioning
confidence: 99%
“…Furthermore, some important evolutionary forces and actions should be considered when sustainable forest management and adaptive silviculture are applied in order to face climate change [72] [30]: 1) evolutionary dynamics of forest trees;…”
Section: Adaptive Forest Management and Silviculture-conservation Measuresmentioning
confidence: 99%
“…Simulation of stand dynamics of infested pine stands reproduces logically the influence of M. hellenica on the growth and mortality of P. brutia according to the currently available scientific information (Ye il et al 2005;Gallis 2007;Petrakis et al 2010Petrakis et al , 2011. Since the influence of the scale insect on P. brutia growth was based on tree-level measurements (Ye il et al 2005), the use of an individual-tree growth model made it possible to directly incorporate the negative effect of the scale insect on tree diameter increment.…”
Section: Forest Management Optimizationmentioning
confidence: 99%
“…For this reason, it has been intentionally introduced at many natural pine forests in these countries and its population has increased locally [ 3 , 4 , 5 ]. Second, it is a pine pest as it feeds on pine sap and can cause increment loss, desiccation, branch dieback, increasing crown transparency and tree decline [ 5 , 6 , 7 , 8 , 9 ]. Furthermore, Petrakis et al [ 9 ] showed that the giant pine scale can cause decrease in diversity of pine-forest-related insects.…”
Section: Introductionmentioning
confidence: 99%